2012
DOI: 10.1186/1687-9856-2012-25
|View full text |Cite
|
Sign up to set email alerts
|

Medullary thyroid cancer in a 9-week-old infant with familial MEN 2B: Implications for timing of prophylactic thyroidectomy

Abstract: BackgroundPatients with Multiple Endocrine Neoplasia type 2 (MEN 2) are at high risk of developing aggressive medullary thyroid carcinoma (MTC) in childhood, with the highest risk in those with MEN type 2B (of whom >95% have an M918T RET proto-oncogene mutation). Metastatic MTC has been reported as young as 3 months of age. Current guidelines recommend prophylactic thyroidectomy within the first year of life for MEN 2B.Patient findingsWe report a 9-week-old infant with MTC due to familial MEN 2B. A full-term m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Germline activating RET mutations implies that mutant RET receptors are constitutively activated once being naturally expressed, which for C cells probably occur at the progenitor stage in pharyngeal endoderm or in precursor cells present in the ultimobranchial epithelium. In line with this assumption, germline RET 918 mutation may cause metastatic MTC with clinical manifestations already in infancy [70]. For germline mutations associated with a less aggressive MTC than 918 it is conceivable that RET is activated in the same developmental stage.…”
Section: Developmental Aspects Of Mtcmentioning
confidence: 80%
See 1 more Smart Citation
“…Germline activating RET mutations implies that mutant RET receptors are constitutively activated once being naturally expressed, which for C cells probably occur at the progenitor stage in pharyngeal endoderm or in precursor cells present in the ultimobranchial epithelium. In line with this assumption, germline RET 918 mutation may cause metastatic MTC with clinical manifestations already in infancy [70]. For germline mutations associated with a less aggressive MTC than 918 it is conceivable that RET is activated in the same developmental stage.…”
Section: Developmental Aspects Of Mtcmentioning
confidence: 80%
“…Cancer is often diagnosed in the teens or twenties in MEN2b and rarely at this young age in MEN2a. Notably, the youngest reported case in MEN2b was in a 9-week-old infant [70], and a case seen by one author was found at autopsy in a 6-week-old child. These findings suggest that the further mutations needed for carcinogenesis may in some cases occur during foetal life.…”
Section: Medullary Carcinoma and Mixed C And Follicular Cell Tumoursmentioning
confidence: 99%
“…The problem is that most of MEN2B patients carry de novo mutations. Shankar et al highlights prophylactic thyroidectomy in 9 weeks old infant with familial MEN2B in whom microscopic MTC has been already revealed 19 . An international, multicentre, retrospective study including 338 patients with MEN2B confirmed a significant difference in remission status between patients who underwent thyroidectomy before and after the age of 1 year 20 .…”
Section: Discussionmentioning
confidence: 99%